The Impact of Baseline Pain Intensity on the Effectiveness of Whole-Body Electromyostimulation (WB-EMS) for Nonspecific Chronic Back Pain. - Konrad, Karl L.; Weißenfels, Anja; Birkenmaier, Christof; Baeyens, Jean-Pierre; Kemmler, Wolfgang; Wegener, Bernd (Cureus, 2024)
INTRODUCTION: Recent clinical studies confirmed that whole-body electromyostimulation (WB-EMS) training is a safe and time-efficient therapeutic method for patients with nonspecific chronic back pain (NSCBP). However, significant variations in initial pain intensity among subjects in these studies have been observed. This study aims to determine if patients with differing initial pain intensities experience varying degrees of benefit from WB-EMS and to assess the overall correlation between initial pain levels and pain reduction. METHODS: Pain intensity datasets from two studies were combined. The pooled data included 121 NSCBP patients (38 males and 83 females) with an average age of 55.1 years (±11.8 years). Data was categorized by baseline pain intensity on the numeric rating scale (NRS) into seven groups: 0 to 2, >2 to 3, >3 to 4, >4 to 5, >5 to 6, >6 to 7, and >7. Both absolute and relative changes were analyzed. Additionally, a Spearman rho correlation test was performed on the entire dataset to evaluate the relationship between initial pain level and pain reduction. RESULTS: Significant improvements were noted across all NRS11 categories, with strong effect sizes (p) in all classes above 2, ranging from 0.56 to 0.90. The >7 category exhibited the highest rate of clinically significant changes (80%) and an average improvement of 3.72 points. The overall group from >1 to 10 showed an average improvement of 1.33 points, with 37% of the participants experiencing clinically significant improvements. The Spearman rho correlation test revealed a moderate positive relationship between initial pain level and pain reduction (r_s = 0.531, p < 0.001), indicating that, generally, higher initial pain levels are associated with greater pain reduction. CONCLUSION: The findings support the hypothesis that NSCBP patients with higher baseline NRS values benefit more substantially from WB-EMS. Those with NRS values above 7 show the greatest improvement and highest rate of clinical significance. The overall positive correlation between initial pain intensity and pain reduction further underscores the efficacy of WB-EMS in managing NSCBP across different pain intensities.
EVALuna2:571032